Keyless Image Encryption using Hash Maps - Monga, Anchal; Papola, Anubhooti (International Journal of Computer Sciences and Engineering, 2025)
To develop the security, a new image encryption method that uses a keyless approach for image encryption is proposed. Keyless approach increases the ability of the system from various types of attacks as compared to the asymmetric keys that are vulnerable to various types of attacks. For security check of the system hash algorithms (MD5 and SHA128) are applied which checks whether the image transmission over the web is manipulated in between the transfer from sender to the receiver. The image is encrypted in such a way that it is not an easy task for the third party to recognize or create the original image by just seeing the encrypted image. Before the transfer of an image SHA128 and MD5 of the image is calculated. After the decryption of the image if SHA128 and MD5 of the system matches the image is not manipulated otherwise it is manipulated. So the Keyless approach, SHA128 and MD5 together increases the overall security of the system and make the system more secure by protecting it from different types of attacks. The outcome shows that the value of error matrix, PSNR is increased by approximately 8% and the values of MSE is about 31% of the encryption using divergent illumination and asymmetric keys which shows that the result are good in comparison of the encryption using divergent illumination and asymmetric keys.